2019
DOI: 10.2478/pjst-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry Indices in Female Runners as Predictors of Running Velocity

Abstract: Introduction. This paper aimed to establish relationships between the level of functional and dynamic asymmetry in advanced and intermediate-level runners and running velocity. Furthermore, evaluation of dynamic symmetry (running and vertical jump) was made using indices, taking into account the continuous character of the signals of the ground reaction force and angular positions in individual joints of the lower limb.Material and methods. Symmetry was assessed in a group of 12 Polish elite female middle-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Sports can be classified from various points of view, but the scientific field lacks a categorization that would include the predominant character of physical activity due to its frequency during sports performance. Cyclic sports predominantly involve periodically repeated movements such as medium to long-distance running, which may hypothetically lead to a balanced unilateral load on the body with low inter-limb strength asymmetry [ 13 , 14 , 15 ]. Conversely, Meyers et al [ 16 ] reported that running biomechanics are generally symmetric; however, some kinetic asymmetry has been detected in healthy young boys.…”
Section: Introductionmentioning
confidence: 99%
“…Sports can be classified from various points of view, but the scientific field lacks a categorization that would include the predominant character of physical activity due to its frequency during sports performance. Cyclic sports predominantly involve periodically repeated movements such as medium to long-distance running, which may hypothetically lead to a balanced unilateral load on the body with low inter-limb strength asymmetry [ 13 , 14 , 15 ]. Conversely, Meyers et al [ 16 ] reported that running biomechanics are generally symmetric; however, some kinetic asymmetry has been detected in healthy young boys.…”
Section: Introductionmentioning
confidence: 99%
“…The postural classification according to gender is frequently overlooked as a trigger factor of injuries by a previous study (Meshkati et al, 2010). Despite other studies clarifying that postural classification has no significant effect on injury (Buist et al, 2010), however, different pieces of training management in individual cases (Anggraeni et al, 2019) often result in improper load (Kusuma et al, 2018) and contribute to a high risk of injury (Tabor et al, 2019). Other findings highlight differences impact of age and gender on injuries (Sterkowicz-Przybycien & Fukuda, 2016), which are related to physical fitness, motor coordination, and technical quality (Subekti et al, 2020), and as factors that may underlie biomechanical movement in Pencak Silat to prevent injuries incidences (Zheng et al, 2020;Kusuma, 2021b),…”
Section: Introductionmentioning
confidence: 92%